Ninjin’yoeito ameliorated PPE-induced pulmonary emphysema and anxiety/depressive-like behavior in aged C57BL/6J mice - Shimoyama, Taiki; Kaneda, Marisa; Yoshida, Shota; Michihara, Seiwa; Fujita, Nina; Han, Li-kun; Takahashi, Ryuji (Frontiers in Pharmacology, 2022)
The prevalence of chronic obstructive pulmonary disease (COPD) is increasing in the elderly. COPD is a chronic respiratory disease characterized by airway remodeling and alveolar emphysema. COPD patients are also at high risk for mental illnesses such as depression and anxiety. Ninjin’yoeito (NYT) is prescribed to patients with conditions such as post-illness and postoperative weakness, fatigue, poor appetite, skin rash, cold hands and feet, and anemia. In addition to traditional uses, NYT is also prescribed as a therapeutic drug for poor functioning of the digestive organs, respiratory organs, and urinary organs. NYT is also known to have an antioxidant effect. The objective of this study was to investigate whether NYT could ameliorate COPD-induced lung injury and anxiety/depression in C57BL/6J-Aged mice exposed to porcine pancreatic elastase (PPE). While intratracheal administration of PPE Induced emphysema in elderly mice, long-term administration of NYT suppressed the pathology. NYT was also found to suppress the apoptosis and oxidative stress caused by PPE. In addition, long-term administration of NYT in three types of behavioral studies was found to ameliorate PPE induced depressive-like behavior. These results suggest that NYT has a therapeutic effect on emphysema and the behavioral abnormalities caused by PPE.